Impacto do uso da ventilação mecânica não invasiva profilática na funcionalidade de pacientes no pós-operatório cardíaco: um ensaio clínico - Araújo Filho, Amaro Afrânio de (2017)
Introduction: During cardiac surgery several factors contribute to the development of pulmonary complications and the installation of postoperative comorbidities. Non-invasive Ventilation (NIV) is being used as promising therapeutic instrument to improve the functionality in this cases. Objective: To evaluate the functional capacity of patients in the postoperative period of myocardial revascularization and heart valve replacement submitted to non-invasive prophylactic ventilation. Method: Randomized controlled clinical trial developed in four groups of patients submitted to two cardiac surgeries: Revascularization and Valve Replacement. It was enrolled patients of both genders, aged 20 to 70 years. In the revascularized group, the sample consisted of 40 patients, assigned to the Experimental Group (GE) with 21 patients and Control Group (CG) with 19 patients. The group undergoing valve replacement was composed of 50 patients, 25 in the GE and 25 in the CG. At the time of hospital admission, the patient underwent a preoperative evaluation, which included patient identification, vital signs, clinical diagnosis, type of surgery, personal history, medication and ejection fraction and Functional Independence Measure (MIF). After the surgical procedure, the patients were referred to the Intensive Care Unit (ICU) and submitted to the standard physiotherapeutic treatment. Patients enrolled in experimental groups, also used NIV in the CPAP mode, 3 times within the first 26 hours after extubation, with positive pressure of 10 cmH2O and treatment duration of 1h each application. A functional reevaluation was made on the 3rd and 5th postoperative day (POD) and in the 7th POD/ discharge hospital day, besides the functional evaluation, the 6-minute walk test (6MWT) and gait velocity test (T10) was performed. It was also monitored the length of surgery, extracorporeal circulation, ICU and hospital stay, in addition to the postoperative ejection fraction of both groups. Results: In the group of revascularized patients, the TC6 analysis presented a difference between groups, where the GC 207.05 ± 68.8 meters and the GE 284.73 ± 94.8 meters (p = 0.006). The variable T10 also presented difference, where the GC 0.68 ± 0.22 m / s and the GE 1.08 ± 0.39 m / s (p <0.0001). The total MIF at hospital discharge was 117.19 ± 11.04 and the GC was 82.52 ± 13.26 (p = 0.01). There was no difference in ICU and hospital admission times between groups. The heart valve replacement patients groups, the 6MWT analysis also showed a significance diference between groups, the GC 264.34 ± 76 meters and the GE 334.07 ± 71 meters (p = 0.002). On the other hand, the analysis of T10, MIF and ICU and hospital admission times did not present differences between the groups. Conclusion: NIV as a therapeutic resource proved to be effective, suggesting an improvement in the functionality of the patients studied in the postoperative period of cardiac surgery, however, it did not influence the length of ICU stay or the general time of hospitalization of the patients with cardiopathy. Brazilian Registry of Clinical Trials RBR - 8bxdd3.